The Pandemic Crisis and the Resulted Risks for the Fully Funded Pension Funds in Central and Eastern Europe - Милев, Жеко (Научни трудове, 2021)
The pandemic crisis strongly hit the capital markets at the beginning of 2020. The value of most of the financial assets dropped significantly in the first quarter of the year, which resulted in poor returns of the portfolios managed by the pension funds in Europe. However, the reaction of the central banks was immediate – the liquidity supplied to the financial markets was unique in its amount. The prices of most of the blue-chip equities and triple A bonds have been rising since the second quarter of the year. Did pension funds in Central and Eastern Europe manage to recover losses incurred at the beginning of the year and what are the main risks for them in the short and in the long term taking into account the monetary policy stance followed by the European central bank and The Federal Reserve? These are the basic issues on focus of the current research. The aim of the paper is to show that pandemic crisis has immediate and strong effect on the investment results of the pension funds but only in the short term. The policy followed by the central banks could have far deeper consequences on fully funded pension schemes and insured individuals.